Use of Fruit Essential Oils to Assist Forest Regeneration by Bats - Bianconi, Gledson V. [UNESP]; Suckow, Urubatan M. S.; Cruz-Neto, Ariovaldo P. [UNESP]; Mikich, Sandra B. (Wiley-Blackwell, 2012)
Frugivorous bats can be attracted with essential oils from ripe chiropterochoric fruit. We evaluated the efficiency of these oils to attract bats in degraded areas within the Atlantic Rain Forest, particularly pasture and agricultural land. We hypothesized that induction units (IUs), each containing a rubber septum impregnated with oil, would have more bat activity than their respective control units (CUs; without the oil). To test this hypothesis we monitored bat flight activity with night-vision infrared visors in eight IU and CU from August 2006 to July 2007. We also verified the probability of arrival of chiropterochoric seeds by analyzing the diet of bats captured in a neighboring forest area. Our initial hypothesis that units with odor would lead to greater bat activity was confirmed. Results indicated a rich community of fruit-eating bats, and dietary analysis revealed a huge potential for dispersion of a vast amount of seeds from different plant species at the IU. Although our study does not reveal with certainty which bat species are attracted to the oil, the flying patterns coincide with those described for the foraging behavior of fruit-eating phyllostomids. Furthermore, the fact that the bats spend more time flying around the odor source compared to flying time around CU suggest an increase in seed rain. Taken together, these results suggest that the use of essential oils from chiropterochoric fruits induces a qualitative and quantitative increase in seed dispersal in areas that otherwise would not be frequently visited by frugivorous bats.
Keywords: Atlantic Forest; bat attraction; conservation biology; frugivory; fruit-eating bats; fruit odors; restoration; seed dispersal